THE FUTURE OF EPIDEMIC CONTROL: EVALUATING THE PHARMACOLOGICAL, CLINICAL, AND SOCIOECONOMIC LANDSCAPE OF MODERN HIV PRE-EXPOSURE PROPHYLAXIS - Pawlak, Kornel; Stępiński, Marcin; Dobrowolska, Julia; Krężołek, Marta; Balicki, Mateusz; Kamyszek, Filip; Kaczmarczyk, Paula; Palus, Alicja; Zynek, Oliwia; Arkuszyński, Tomasz (International Journal of Innovative Technologies in Social Science, 2026)
Background: Pre-exposure prophylaxis (PrEP) has fundamentally transformed the global HIV prevention paradigm. Over the past decade, the strategy has evolved from adherence-dependent daily oral regimens to ultra-long-acting injectable modalities, addressing the most critical behavioral barriers to achieving widespread epidemic control.Objective: This comprehensive review synthesizes the current literature on the molecular evolution, clinical efficacy, pharmacokinetic variables, and implementation challenges of PrEP. It traces the trajectory from early daily oral TDF/FTC interventions to first-in-class, ultra-long-acting capsid inhibitors like lenacapavir.Methods: An exhaustive review of recent literature- incorporating articles published in PubMed, Cochrane, and global health databases between 2019 and 2026- was conducted. This included an analysis of pivotal clinical trials (e.g., DISCOVER, HPTN 083/084, PURPOSE 1 and 2), real-world implementation data, WHO guidelines, and recent systematic reviews on pharmacoeconomics in sub-Saharan Africa.Results: While daily oral TDF/FTC and TAF/FTC demonstrate high biological efficacy, their real-world success is heavily compromised by the "adherence-efficacy paradox." Long-acting injectable cabotegravir (CAB-LA) and lenacapavir offer superior protection by decoupling prevention from daily routines. Recent data from PURPOSE 1 demonstrate 100% efficacy of lenacapavir in cisgender women, while PURPOSE 2 showed a 96% reduction in HIV incidence among cisgender men and transgender populations. However, novel challenges have emerged, including pharmacokinetic modifiers (e.g., the vaginal microbiome's impact on local drug efficacy), the management of the "pharmacokinetic tail," and severe economic barriers.Conclusion: The future of HIV prevention relies on a diversified, equity-driven, person-centered approach. Ensuring global access to long-acting technologies, facilitated by aggressive voluntary licensing and integrated differentiated service delivery models, remains the primary challenge in utilizing PrEP to achieve the World Health Organization’s goal of ending the HIV epidemic.